En route to a masterpiece a collection of sketches of five modernists - Andaya, Mari Jina David (2012)
En route to Masterpiece is a collection of sketches that features five modernists and the creation of their masterpieces that make them prominent in the Philippine Art scene. Each narrative talks about the artists' visual encounters with their subjects, how their eyes perceive different forms beyond the surface of objects they stumble upon, and how these objects persist in their thoughts for a long period of time. The life stories also include their struggles as they go through life, as they evolve artistically, and as they imbibe the eccentricities of their milieu. The creative writing dissertation starts with an Introduction that discusses the nontraditional use ekphrasis and skenographia in all five sketches, my rationale for choosing to write about visual artists and five maestros, and why the narratives can be classified as sketches. The second part, which contains the creative work, includes the following sketches: 1. Barungbarong - talks about Mauro Malang Santos's experiences as an artist as the head of the Santos clan; 2. Galloping Horses - is about Charito Bitanga's life as a graduate student of Cranbrook Academy of Art; 3. Lakbay Diwa - recounts Filemon Dela Cruz's immersion with the B'laans; 4. Fish Vendor - is Norma Belleza's life as a wife and an artist; and 5. Nuestra Señora - is about Mario Parial's experiences that lead to the making of his Marian series.
"March 2012."
Thesis (Ph.D. Creative Writing)--University of the Philippines Diliman.
Keywords: Narration (Rhetoric).; Ekphrasis; Philippine Literature (English).